Ta có:
\(P\left(x\right)=2x\left(x^3-3x+1\right)-\left(x^3-3x+1\right)+x^2-4\)
Do đó: \(P\left(a\right).P\left(b\right).P\left(c\right)=\left(a^2-4\right)\left(b^2-4\right)\left(c^2-4\right)\)
Ta có:
\(\left(x-a\right)\left(x-b\right)\left(x-c\right)=x^3-3x+1\)
\(\Rightarrow\left\{{}\begin{matrix}a+b+c=0\\ab+ac+bc=-3\\abc=-1\end{matrix}\right.\)
C1: \(\left(a^2-4\right)\left(b^2-4\right)\left(c^2-4\right)=\left(abc\right)^2-4\left(a^2b^2+b^2c^2+c^2a^2\right)+16\left(a^2+b^2+c^2\right)-4^3\)
\(=1-4.9+16.6-4^3=-3\)\(\Rightarrow P\left(a\right).P\left(b\right).P\left(c\right)=-3\)
C2: Biến đổi thêm một chút
Ta có: \(a,b,c\ne0\) nên
\(a^3-3a+1=0\Leftrightarrow a\left(a^2-3\right)+1=0\)\(\Rightarrow a^2-3=\dfrac{-1}{a}\)
Tương tự...
\(\Rightarrow P\left(a\right).P\left(b\right).P\left(c\right)=\left(-\dfrac{1}{a}-1\right)\left(-\dfrac{1}{b}-1\right)\left(-\dfrac{1}{c}-1\right)\)
\(=-\left(\dfrac{1}{a}+1\right)\left(\dfrac{1}{b}+1\right)\left(\dfrac{1}{c}+1\right)\)\(=-\dfrac{a+1}{a}.\dfrac{b+1}{b}.\dfrac{c+1}{c}=abc+ac+bc+ab+a+b+c+1=-1-3+1=-3\)